Relative Strenght Index, Moving Average Convergence-Divergence on Stock Performance and Fundamental Analysis as Moderating - Ronni Andri Wijaya; Yamasitha Yamasitha; Elfiswandi Elfiswandi; Lusiana Lusiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
This study aims to determine the effect of Relative Strength Index (RSI) and Moving Average Convergence-divergence (MACD) on stock performers with Debt to Equity Ratio (DER) as a Moderation variable in Financing companies listed on the Indonesian Stock Exchange (IDX). Sampling in the study using purpose sampling method obtained 14 companies with time series data. The analysis method used in this study is multiple linear regression analysis using eview. The results show that Relative Strenth Index (RSI) partially has a positive and significant effect on stock performance, Moving Average Convergence-divergence (MACD) partially has a positive and significant effect on stock performance, Relative Strenth Index (RSI) has a positive and significant effect on stock performance. which is moderated by Debt to Equity Ratio (DER), Moving Average Convergence-divergence (MACD) has a positive and significant effect on the Performance of Shares moderated by Debt to Equity Ratio (DER).